x平方—2x+3
x平方—2x+3
x平方-3[2x-5(x平方-x+1)]
(x平方-1)的平方-(2x+2)平方 (x平方+x)(x平方+x-2)-3(x平方-1)的平方-(2x+2)平方(x平方+x)(x平方+x-2)-3分解因式
4x的平方—8x+5-3x的平方=6x-2
5x平方-[x平方 (5x平方-2x)-(2x平方-3x)]其中x=-2分之一
(1-x/3-x)平方除以x平方-6x+9/9-x平方*1/x平方-2x+1
化简求值.(3X平方)平方—2X平方(X+1)—3X(X平方—7) X= - ½
分式约分 一、x平方-2x分之x+1分之x平方-1 二、6x平方分之3x平方+3xy——要过程
(x平方-3)平方-x(x平方-3)-2x平方
x的平方×(-x)的平方×(-2x的平方)+(-2x的平方)3次方
2x平方-5x+x的平方+4x-3x的平方-2
(-2x平方+3x)-[5x-(2x平方+1)-x平方] 化简
方程2/X平方+X+3/X平方-X=4/X平方-1
填空:2x平方-3x+( )=2(x+( )平方
|x平方-3|小于|x平方-2x|怎么解
化简:(x+y)平方-3(x平方-2y平方)
2x平方+(x+2)平方+(x+4)平方+(x+6)平方=(3x+2)(2x+6)
(x平方+4x+8)平方+3x(x平方+4x+8)+2x平方因式分解